Reframing Modal Tradition: Javanese Laras and Pathet in Contemporary Composition - Sa'adah , Sufi Ikrima (Indonesian Scientific Publication, 2024)
This article explores the transformation of Javanese modal systems laras, pathet, and garap within contemporary music practices. It investigates how these core concepts, traditionally embedded in the structure and expression of gamelan music, are preserved, adapted, and recontextualized in modern acoustic, electronic, and hybrid compositional environments. Methodologically, the study applies a comparative analytical approach, combining empirical data from tuning measurements and seleh tone mapping with case studies from Rahayu Supanggah, Lou Harrison, and Gamelan Son of Lion. Tuning deviations across gamelan sets are analyzed, highlighting the flexibility of laras and the structural logic of pathet. The study also examines how garap enables interpretive variation in performance and how these modalities are translated into Just Intonation, orchestral writing, and campursari arrangements. Key results show that Javanese modality maintains coherence despite cross cultural adaptations. Modal identity is preserved through behavioral cues, tonal relationships, and ornamentation, even when transposed into Western or electronic idioms. The interaction of structure and flexibility particularly through garap allows Javanese modes to thrive in modern contexts without sacrificing expressive depth or cultural meaning. These findings suggest that Javanese modal systems are highly adaptable, offering a valuable framework for global music composition and intercultural dialogue. The research contributes to both ethnomusicology and composition studies by reframing Javanese modality as a resilient, integrative, and innovative force in 21st century music.